The Influence of Decision-Making Style, Market Sensing, and Marketing Technology on Organizational Performance of MSMEs in Indonesia - Aina Dhiya Qalbaha; Yuriska Halmaera; Claristy Yocelyn; Queen Mayomy (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia’s economy; however, they face increasingly complex competitive pressures and rapid technological change. These conditions require MSME owners and managers to possess adequate managerial capabilities and technological competencies in order to improve organizational performance. This study aims to examine the influence of Decision-Making Styles, Market Sensing Capability, and Marketing Technology Capability on the Organizational Performance of MSMEs in Indonesia. The research employs a quantitative approach using a survey method. Data were collected through online questionnaires distributed to 66 MSME owners or managers selected using purposive sampling. The research instruments were tested for validity and reliability, while data analysis was conducted using descriptive statistics and multiple linear regression with the assistance of SPSS software. The results indicate that Decision-Making Styles, Market Sensing Capability, and Marketing Technology Capability simultaneously have a significant effect on Organizational Performance. The coefficient of determination (R Square) value of 0.818 shows that these three independent variables explain 81.8% of the variance in MSME organizational performance, while the remaining 18.2% is influenced by other factors outside the research model. Partially, the findings reveal that only Marketing Technology Capability has a significant effect and is the most dominant factor influencing organizational performance. In contrast, Decision-Making Styles and Market Sensing Capability do not show a significant individual effect. These findings suggest that the effective utilization of marketing technology plays a crucial role in supporting strategic implementation and improving MSME performance. This study is expected to contribute theoretically to MSME management literature and provide practical insights for MSME practitioners and policymakers in formulating strategies to enhance organizational performance in the digital era.